Ideological quests of the russian intelligentsia of miscellaneous ranks and their reflection in the literature about the “new people” at the turn of the 1860–70s - Liliia Iliasova (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2020)
The article analyses the novels about the “new people” published at the turn of the 1860s and 1870s. These are Znameniia vremeni (‘Signs of the time’) by D. L. Mordovtsev, Shag za shagom (‘Step by step’) by I. V. Omulevsky, Nikolai Negorev, ili Blagopoluchnyi rossiianin (‘Nikolai Negorev, or the Prosperous Russian’) by I. A. Kushchevsky. The aim of the study is to identify the ideological agenda of the Russian intelligentsia of miscellaneous ranks (Rus. разночинная интеллигенция) of that time. The literature on the “new people”, starting from the novel by N. G. Chernyshevsky Chto delat’? (‘What to do?’), attempted to provide ideological guidelines for the new generation; the novels of this kind were “manuals” for young intellectuals, where they looked for answers to questions about what to they should do and be like. Due to the clearly opinionated nature of these texts, they are a valuable historical source for the study of the ideology of intelligentsia, its intellectual and moral quests. In historiography, these novels were described mainly in the context of the history of the Russian literature and literary criticism, but were not used in an integrated way as a specifi c topic of research in the light of the study of world outlook of intelligentsia, which makes this article particularly relevant. The main part of the article describes plot-related and thematical units, shows the features of personalities of the characters of the novels, studies the ideas that they proclaim. The article concludes that these novels refl ected the mindset of the intelligentsia of the period of transition, i.e. between the Sixtiers and the Narodniks, and were incorporated in the process of development of its ideology.